Light Curing Devices-A Clinical Review - Singh, Tarun Kumar; Ataide, Ida; Fernandes, Marina; Lambor, Rajan T. (Journal of Orofacial Research, 2011)
Curing light are an integral part of the daily practice of restorative dentistry. The mode of curing has regularly changed during the last 30 years. The different types of polymerization sources available today are Quartz-tungstenhalogen (QTH), Plasma arc (PAC), Argon laser and light emitting diode (LED) curing lights. This clinical review is principally focussed on assessing the clinical relevance of curing systems available; in terms of their selection and maintenance in the dental operatory; thus optimizing their clinical performance.